Sexual selection and signalling in the lizard Platysaurus minor - Lewis, Belinda Ann (My University, 2008)
ABSTRACT Sexual selection may influence aspects of male morphology associated with territoriality, female choice, aggression and contest success. Attributes that are most commonly selected for include body size, condition, weaponry, endurance and bright coloration. I investigated the relationships between morphology, use of space and home range quality, and access to females. Specifically, I examined the relationships between colour, body size and condition, and whether morphology could predict aggression or contest success. Colour spectral data were analyzed using both traditional measures of colour (hue, chroma, brightness) and principal components. Males with darker, more saturated chests, and more saturated throats, had larger home ranges. Home range quality, as determined by refuge number and prey availability, was associated with blue chests and blue throats and chests, respectively. Males with larger home ranges had higher numbers of associated females and spent more time courting females. Larger males in better condition had darker, more saturated chests. Males in better body condition were also more aggressive. There was a consistent trend for larger males to win more contests, but this relationship was only significant in analyses using traditional measures of colour.
Keywords: signal; colour; reptile; communication; reproductive strategy